Effect of Chromium(III) on the Sulphur(IV) Oxidation Catalysed by Manganese(II) under Conditions Representative for Atmospheric Waters - Wilkosz I. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The kinetics of the S(IV) oxidation in aqueous solutions in the presence of Cr(III) and Mn(II) ions was studied and the influence of Cr(III) ions on the S(IV) oxidation catalysed by Mn(II) ions was determined. Laboratory experiments were carried out at concentrations of reactants and pH found in atmospheric waters in heavily polluted atmospheres. The kinetic law parameters, i.e. the observed rate constants and the reaction orders with respect to S(IV) concentration, were determined. The results obtained for the S(IV) oxidation in the presence of Cr(III) ions only, show that Cr(III) ions have little catalytic effect on the S(IV) oxidation. Under conditions studied, this effect was several times smaller than that of Mn(II) ions. The S(IV) oxidation rate in the simultaneous presence of Mn(II) and Cr(III) ions was greater or smaller than that in the presence of Mn(II) ions only, depending on the reaction conditions. However, it was always smaller than expected from the sum of the two individual rates (in the presence of Mn(II) ions alone and in the presence of Cr(III) ions alone), which shows that there is antagonism between Mn(II) and Cr(III) ions. The magnitude of this antagonistic effect depends on an initial pH and concentrations of both Mn(II) and Cr(III) ions. At low values of these parameters, the antagonistic effect is rather small, but at higher values of them, it may be strong.